Identifying Financial and Non-Financial Factors as the Determinant of Sukuk Rating in Indonesia - Datien Eriska Utami (Shirkah: Journal of Economics and Business, 2019)
The present study aims to identify financial and non-financial factors as the determinant variables of Indonesian companies' Sukuk ratings between 2014 and 2017. Five independent variables, i.e. firm size, profitability, leverage, guarantee status, and types of Sukuk, are involved in this study with Sukuk rating as the dependent variable. This study employed secondary data in the form of sixty-eight (68) Sukuk publications as the sample. The Sukuk publications observed in this study were still in circulation during the observation years obtained from Otoritas Jasa Keuangan (OJK/ Financial Services Authority) websites, annual reports of companies listed in Indonesia Stock Exchange, and PT Pefindo website. By utilizing Multinomial Logistic Regression, this study reveals that the financial factor, the profitability, had a significant effect on the Sukuk rating. Moreover, it also shows that the non-financial factor influencing the Sukuk rating was the guarantee status. On the contrary, the variables of firm size, leverage, and types of Sukuk did not affect the Sukuk rating.Â Keywords: firm size, profitability, leverage, guarantee status, types of Sukuk, Sukuk rating